We are the ants - Hutchinson, Shaun David (Simon Pulse, 2016)
Henry Denton has spent years being periodically abducted by aliens. Then the aliens give him an ultimatum: the world will end in 144 days, and all Henry has to do to stop it is push a big red button. Only he isn't sure he wants to. Life hasn't been great for Henry: his mom is held together by a thin layer of cigarette smoke; his brother is a jobless dropout. And Henry is still dealing with the grief of his boyfriend's suicide last year. Weighing the pain and the joy that surrounds him, Henry can choose to save the planet... or let it be destroyed.